PENGEMBANGAN VARIASI PENYERANGAN PERMAINAN BOLAVOLI PADA EKSTRAKURIKULER DI SMP NEGERI 17 MALANG - Huda, Alanse Taufiqul; Winarno, M. E.; Tomi, Agus (Fakultas Ilmu Keolahragaan Universitas Negeri Malang, 2017)
Abstract: The purpose of the volleyball game is dropping the ball as fast as possible inthe opposite field passes over the net using the entire limb. This product is valid andpractical to be used for volleyball game attacks variation training in extracurricularactivities in SMPN 17 Malang. Based on the results of the needs analysis showed thatthe strategy of attacking done very lacking, extracurricular participants had never beentaught the material about attacking strategy in volleyball small group of test data obtained88.37% and the results of the data analysis of a large group trial gained an averagepercentage of 81.32 %. The result of the product development strategy of attacking gameof volleyball for participants extracurricular volleyball high school students first, amongothers: (1) the strategy of attacking volleyball in the manual according to the needs ofextracurricular participants junior high students, (2) to see the strategy of attacking gameof volleyball made with color image and there is information which explain attackingprocess variation from the current position to receive smash.Keywords: attacking variation, volleyball, developmentAbstrak: Tujuan dari permainan bolavoli adalah menjatuhkan bola secepat mungkin dilapangan lawan melewati atas net menggunakan seluruh anggota badan. Produk ini validdan praktis digunakan untuk latihan variasi penyerangan permainan bolavoli padakegiatan ekstrakurikuler di SMPN 17 Malang. Berdasarkan hasil analisis kebutuhandiperoleh bahwa strategi menyerang yang dilakukan sangat kurang sekali, pesertaekstrakurikuler belum pernah diajarkan materi strategi menyerang bolavoli data uji cobakelompok kecil diperoleh hasil 88,37% dan dari data analisis uji coba kelompok besardiperoleh rata-rata persentase 81,32%. Hasil produk pengembangan strategi menyerangpermainan bolavoli untuk perserta ekstrakurikuler bolavoli siswa menengah pertamaantara lain: (1) variasi menyerang bolavoli dalam buku panduan sesuai dengankebutuhan peserta ekstrakurikuler siswa menengah pertama, (2) tampilan strategimenyerang permainan bolavoli dibuat dengan gambar yang berwarna dan terdapatketerangan yang menejelaskan proses variasi serangan mulai dari posisi receive sampaisaat smash.Kata Kunci: variasi menyerang, bolavoli, pengembangan